Direct 3D Printing of Flexible Nasal Prosthesis: Optimized Digital Workflow from Scan to Fit. Issue 1 (29th November 2018) - Nuseir, Amjad; Hatamleh, Muhanad Moh'd; Alnazzawi, Ahmad; Al‐Rabab'ah, Mohammad; Kamel, Belal; Jaradat, Esraa
Abstract: A maxillofacial prosthesis is a successful treatment modality to restore missing facial parts. Digital technologies and 3D printing are employed in constructing facial prostheses such as ears; however, their application is still partial, and final prostheses are usually manufactured conventionally using stone molds. This report aims to introduce a complete digital workflow to construct a nasal prosthesis and compare it to the conventional workflow of a patient requiring a nasal prosthesis. A computer tomography scan showing the defect was exported to specialized software to create 3D reconstructions of the patient's face and underlying bone. The nose was digitally designed restoring facial esthetics, anatomy, shape, and skin color. Different skin tones were digitally matched to skin tissues adjacent to the defect area using the Spectromatch system. The design was 3D printed in flexible and colorful material at 16 μm resolution using a 3D printer. External color pigmentations were applied to the nose for optimum esthetics, and the prosthetic nose was sealed in silicone and left to heat polymerize for 15 minutes. The prosthetic nose was retained in place using biomedical adhesive, and the patient was pleased with it. This report proposes a complete digital workflow to directly design and fabricate a prosthetic nose of acceptable esthetics. Such a workflow can lead to enhanced prosthesis reproducibility and acceptability and may become an effective treatment option for treatment of patients with facial defects.